Effect of Season on Crop Growth, Flowering, Synchronization Pattern and Seed Yield in the Parental Lines of Maize (Zea mays L.) Hybrids - SUDIPTA BASU; BHAUMIK; S.P. SHARMA; M. DADLANI (Seed Research, 2026)
Performance of parental line seeds of maize hybrids viz. Ganga-5, Ganga-11, Ganga Safed-2, PHM-1 and PHM-2 was studied in monsoon, winter and spring-summer season (1996-98) for field emergence, vegetative growth, flowering behaviour, synchronization pattern and seed yield. The results indicated that weather conditions, especially temperature and rainfall influenced field emergence and seedling growth in all the seasons. A temperature of 10°C was found critical for seedling growth and development of maize under sub-optimum conditions prevalent in winter and spring-summer seasons. Vegetative growth, flowering behaviour [days to flowering, duration of flowering, anthesis silking interval (ASI)], synchronisation pattern and seed yield was highly influenced by season, while number of leaves and duration of tasselling remained stable over the seasons. The results revealed the feasibility of seed production of hybrids; PHM-1 and PHM-2 in all the seasons and of Ganga5, Gangall and Ganga Safed2 only in monsoon season and with adoption of flowering manipulation practices in winter and spring-summer seasons under North Indian conditions.